What Is Happening on Twitter? A Framework for Student Research Projects With Tweets. (1st January 2021) - Boehm, Frederick J.; Hanlon, Bret M.
Abstract: We draw on our experiences with mentoring two students to develop a framework for undergraduate research projects with Twitter data. Leveraging backward design principles, we share our learning objectives and rubric for summative assessments. To illustrate the value of Twitter as a data source, we detail methods for collecting and analyzing tweets. We conclude by emphasizing how Twitter text analysis projects enable students to formulate original research questions, collect and analyze data, and communicate findings and their implications. Supplementary materials for this article are available online.